2017
DOI: 10.1038/s41598-017-01180-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key proteins and pathways in cadmium tolerance of Lactobacillus plantarum strains by proteomic analysis

Abstract: Our previous study confirmed the protective potential of Lactobacillus plantarum (L. plantarum) strains in alleviation of cadmium (Cd) toxicity in vivo and demonstrated that the observed protection largely depended on the tolerance of the strains to Cd-induced stress. It was also observed that there were significant intra-species differences in Cd tolerance of L. plantarum strains. In this study, we investigated the mechanism of Cd induced stress response of L. plantarum strains using the isobaric tags for rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 66 publications
(83 reference statements)
3
30
0
Order By: Relevance
“…32 According to Ron et al, 1992, cadmium mediates the stress response in the cells, which results in the production of a large number of proteins in response to stress. 33 The cadmium chloride solution was added to Pseudomonas aeruginosa cells to find out the tolerance threshold (Table 3). Cadmium toxicity in the case of bacterial cells has been speculated to be associated with DNA damage via reactive oxygen species generation, which is likely to cause interference in the synthesis of proteins and other metabolites.…”
Section: Bio-mechanism Of Cds Qdsmentioning
confidence: 99%
“…32 According to Ron et al, 1992, cadmium mediates the stress response in the cells, which results in the production of a large number of proteins in response to stress. 33 The cadmium chloride solution was added to Pseudomonas aeruginosa cells to find out the tolerance threshold (Table 3). Cadmium toxicity in the case of bacterial cells has been speculated to be associated with DNA damage via reactive oxygen species generation, which is likely to cause interference in the synthesis of proteins and other metabolites.…”
Section: Bio-mechanism Of Cds Qdsmentioning
confidence: 99%
“…AFE_2018 was proposed to be a putative MBP, and AFE_1839, AFE_2599/AFE_3116, AFE_2600/AFE3117 were suggested to be involved in sulfur metabolism with a potential role in the biosynthesis of cysteine-rich MTs (Dekker et al, 2016 ). Elsewhere, Zhai et al ( 2017 ) used LC/LC-MS/MS with iTRAQ labeling and discovered a putative Cd transporter lp_3327 from Lactobacillus plantarum that was downregulated in the presence of 5 mg/L Cd, which suggests it could be used in an import system. Lastly, Zammit et al ( 2016 ) used DIGE with CyDyes labeling for Cupriavidus metallidurans CH34 grown in the absence and presence of gold, and discovered upregulated putative gold-binding proteins like CupC (Zammit et al, 2016 ).…”
Section: Re-thinking Bioaccumulationmentioning
confidence: 99%
“…However, not all probiotics possess this desirable function, which is closely associated with microbial specificity. A previous study comparing Cd‐resistant L. plantarum CCFM8610 and Cd‐sensitive L. plantarum CCFM191 revealed that Cd tolerance of CCFM8610 might be related to its specific energy conservation mode, cellular defense and repair system, elevated biosynthesis of hydrophobic amino acids in response to Cd exposure, and effective cell wall biosynthesis competence (Zhai et al, ). Metabolic analysis demonstrated that CCFM8610 possessed higher content of osmolytes, effective biosynthesis of extracellular polymeric substances, and more rigid cell membrane structure (Zhai, Xiao, Narbad, & Chen, ).…”
Section: Antioxidative and Immune Regulatory Effects Of Probiotics Unmentioning
confidence: 99%